Inherited retinal diseases: Linking genes, disease-causing variants, and relevant therapeutic modalities. (July 2022) - Schneider, Nina; Sundaresan, Yogapriya; Gopalakrishnan, Prakadeeswari; Beryozkin, Avigail; Hanany, Mor; Levanon, Erez Y.; Banin, Eyal; Ben-Aroya, Shay; Sharon, Dror
Abstract: Inherited retinal diseases (IRDs) are a clinically complex and heterogenous group of visual impairment phenotypes caused by pathogenic variants in at least 277 nuclear and mitochondrial genes, affecting different retinal regions, and depleting the vision of affected individuals. Genes that cause IRDs when mutated are unique by possessing differing genotype-phenotype correlations, varying inheritance patterns, hypomorphic alleles, and modifier genes thus complicating genetic interpretation. Next-generation sequencing has greatly advanced the identification of novel IRD-related genes and pathogenic variants in the last decade. For this review, we performed an in-depth literature search which allowed for compilation of the Global Retinal Inherited Disease (GRID) dataset containing 4, 798 discrete variants and 17, 299 alleles published in 31 papers, showing a wide range of frequencies and complexities among the 194 genes reported in GRID, with 65% of pathogenic variants being unique to a single individual. A better understanding of IRD-related gene distribution, gene complexity, and variant types allow for improved genetic testing and therapies. Current genetic therapeutic methods are also quite diverse and rely on variant identification, and range from whole gene replacement to single nucleotide editing at the DNA or RNA levels. IRDs and their suitable therapies thus require a range of effective disease modelling in human cells, granting insight into disease mechanisms and testing of possible treatments. This review summarizes genetic and therapeutic modalities of IRDs, provides new analyses of IRD-related genes (GRID and complexity scores), and provides information to match genetic-based therapies such as gene-specific and variant-specific therapies to the appropriate individuals.